2021
DOI: 10.34172/jcvtr.2021.20
|View full text |Cite
|
Sign up to set email alerts
|

Is there any association between contrast-induced nephropathy and serum uric acid levels?

Abstract: Introduction: During the recent years, several studies have investigated that hyperuricemia is associated with greater incidence of contrast induced nephropathy (CIN). Most of them are in acute conditions like primary percutaneous coronary interventions. This study aimed to assess the relationship between high serum uric acid and incidence of acute kidney injury in patients undergoing elective angiography and angioplasty. Methods: This prospective study was conducted on 211 patients who were admitted to hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The analysis of 10 of 15 included studies showed that the incidence rate of PC-AKI in the hyperuricemia group was significantly higher than that in the normal uric acid group ( 10 , 18 , 19 , 21 24 , 27 – 29 ). On the contrary, other 5 studies indicated that hyperuricemia was not directly related to the incidence of contrast-induced nephropathy ( 11 , 13 , 20 , 25 , 26 ). The results of the subgroup analysis showed that the overall effect of hyperuricemia was statistically significant, which proved that hyperuricemia was an independent risk factor of PC-AKI, and this is consistent with most of the previously reported results ( 22 24 , 27 – 29 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The analysis of 10 of 15 included studies showed that the incidence rate of PC-AKI in the hyperuricemia group was significantly higher than that in the normal uric acid group ( 10 , 18 , 19 , 21 24 , 27 – 29 ). On the contrary, other 5 studies indicated that hyperuricemia was not directly related to the incidence of contrast-induced nephropathy ( 11 , 13 , 20 , 25 , 26 ). The results of the subgroup analysis showed that the overall effect of hyperuricemia was statistically significant, which proved that hyperuricemia was an independent risk factor of PC-AKI, and this is consistent with most of the previously reported results ( 22 24 , 27 – 29 ).…”
Section: Discussionmentioning
confidence: 93%
“…Hyperuricemia was associated with PC-AKI and suggested that serum uric acid level could be a novel independent predictor of PC-AKI ( 10 , 11 ). However, similar studies were conducted, while controversial results were reported ( 12 , 13 ), and the causal role in AKI remains elusive. Notably, the relevant studies were mainly conducted based on a direct comparison of the uric acid level between the PC-AKI group and the non- PC-AKI group ( 12 ).…”
Section: Introductionmentioning
confidence: 95%
“…Nevertheless, other studies reported conflicting findings. In a study of 211 patients admitted to the hospital for elective coronary angiography or angioplasty, Mirbolouk et al [10] found that the occurrence of contrast-induced nephropathy was not significantly different in patients with normal and high uric acid. Moreover, Pakfetrat et al [11] noted that SUA levels did not significantly differ between those with and without contrast-related AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that increased serum uric acid (SUA) induces AKI in patients undergoing primary percutaneous coronary intervention [6][7][8][9]. Nonetheless, other studies indicate that high uric acid is not associated with AKI in low-risk patients undergoing elective PCI [10,11]. The severity of the disease potentially influences the relationship between hyperuricemia and AKI.…”
Section: Introductionmentioning
confidence: 99%
“…Mirbolouk et al, 18 carried out a comprehensive review and meta-analysis to evaluate the influence of the location of myocardial infarction on the risk of CIN. They discovered that patients who experienced anterior myocardial infarctions faced an elevated likelihood of developing contrast-induced nephropathy (CIN).…”
Section: Variablesmentioning
confidence: 99%